A case of paraneoplastic limbic encephalitis associated with thymoma - Kimura, Naoko; Kuwata, Hiromi; Nagasaka, Satoshi; Ito, Hideyuki; Morita, Takatomo; Maeyashiki, Tatuo (The Journal of the Japanese Association for Chest Surgery, 2010)
A 32-year-old male presented with new-onset memory loss and confusion. Chest radiograph and CT examination revealed an antero-mediastinal mass. No anti-Hu-antibody was found in the serum or cerebro-spinal fluid. Magnetic resonance imaging (MRI) of the brain showed an increased signal and swelling of the hippocampi on FLAIR. Paraneoplastic limbic encephalitis associated with thymoma was subsequently diagnosed. Gradually, his mental status and seizures worsened despite anticonvulsant therapy, and he was intubated and referred to our hospital for combined modality therapy. Surgery was performed. Intraoperative findings included an antero-mediastinal mass which started from the right lobe of the thymus and pleural implants. The tumor and pleural implants were resected passively. Pathological findings identified WHO typeB2 thymoma. After the operation, steroid pulse and radiation therapies were performed. The patient's clinical course improved markedly over the next 3 months. MRI showed a nomal signal, and 10 months after surgery, he was able to return to work.